Pengaruh Kualitas Pegawai Dan Komitmen Organisasi Terhadap Kinerja Pegawai Bagian Sekretariat Pada Dinas Pemadam Kebakaran Dan Penanggulangan Bencana Kabupaten Kutai Kartanegara - Adawiyah, Raudatul (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2017)
This research was to analyze The Influence Of Quality Of Employee And Organizational Commitment To Employee Performance Of Secretariat Fire And Disaster Prevention Office Of Kutai Kartanegara Regency. The results showed that the independent variables have a significant relationship or employee performance variable influenced by variable Quality Employees (X1) and Organizational Commitment (X2). Then the first hypothesis stating that “Variable Quality Employees And Organizational Commitment Affects Employee Performance Secretariat Field At Fire Department And Disaster Mitigation Kutai Kartanegara Regency" accepted and proven truth.From the two partial correlation test results above shows the variable value of the highest quality of employees compared to organizational commitment variable, so that the variable of employee quality is the most dominant variable affecting employee performance. From the description, it can be concluded that the second hypothesis in this study "Allegedly Quality Employees have a dominant influence on Employee Performance”. Keywords: Performance, Organizatonal Commitment